The effect of group art therapy on older Korean adults with Neurocognitive Disorders. (February 2016) - Kim, Hyun-Kyung; Kim, Kyung Mee; Nomura, Shinobu
Highlights: The purpose of this study was to examine the effects of group art therapy on improving the emotional capacities of older Korean adults with Neurocognitive Disorders. This study was undertaken with two original features using life review method: 36 therapy sessions and a wide variety of materials including Korean traditional materials such as rice paper, Korean paints and brushes, and ink sticks. Older Korean adults with Neurocognitive Disorders were shown to have greatly decreased levels of depression and increased levels of self-expression. Abstract: The purpose of this study was to examine the effects of group art therapy on improving the emotional capacities of older Korean adults with Neurocognitive Disorders (ND). In Korea, little research has been conducted on patients with mental disorders in nursing homes to measure the effectiveness of art therapy. Expanding upon previous research, this study tested an art therapy program that included 36 treatment sessions and used a wide variety of materials, including traditional materials, such as rice paper, Korean paints and brushes, and ink sticks. The program's goals were to reduce patients' levels of depression and improve their ability to express themselves. This research analyzed the effect of art therapy using the Short Geriatric Depression Scale and computer analysis of painting patterns. Older Korean adults with ND were shown to have decreased levels of depression and increased levels of self-expression, demonstrating that group art therapy was effective at improving the condition of older patients with ND.